2017
DOI: 10.1080/10428194.2017.1312372
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of treatment and costs associated with transfusion burden in patients with myelodysplastic syndromes

Abstract: Transfusion dependence (TD) among myelodysplastic syndromes (MDS) patients negatively impacts survival and health-related quality of life. We evaluated cost patterns of MDS care during TD and transfusion independence (TI). MDS patients were identified from a US claims database (2008-2013). TD was defined as ≥2 consecutive 8-week periods with ≥1 claim during each, and no interim 56-day period without transfusion; TI as 8 subsequent transfusion-free weeks; and transfusion frequency as the mean interval between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Similar results were reported by an abstract publication, which reported that transfusion dependence predicted increased cost of illness in patients with unselected‐risk MDS 52 . In studies considering only patients with low‐risk MDS, it was also reported that the absence of transfusions was associated with a lower risk of hospitalization and emergency room visits, 40 and that the increase in total costs of care was proportional to transfusion frequency in TD patients 47 …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar results were reported by an abstract publication, which reported that transfusion dependence predicted increased cost of illness in patients with unselected‐risk MDS 52 . In studies considering only patients with low‐risk MDS, it was also reported that the absence of transfusions was associated with a lower risk of hospitalization and emergency room visits, 40 and that the increase in total costs of care was proportional to transfusion frequency in TD patients 47 …”
Section: Discussionsupporting
confidence: 79%
“…After excluding duplicates, 6268 records were screened by assessing title and abstract for eligibility, of which 131 records were selected for full‐text assessment and 97 were excluded for not meeting the inclusion criteria. A total of 12 studies with clinical outcomes other than OS were included 18‐21,25,40‐46 as well as six studies with economic outcomes 40,47‐51 and 10 studies 51‐60 with humanistic outcomes (Figure 2). Included studies on clinical outcomes other than OS are listed in Table 4, 18‐21,25,40‐46 those on economic outcomes are in Table 5, 40,47‐51 and those on humanistic outcomes are in Table 6 51‐61 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, approximately 60-80% of MDS patients will develop anemia at some point during their disease course [12]. Up to 90% of patients with MDS will receive transfusions during their clinical course, and up to 79% of patients with HR-MDS will become transfusion-dependent, although how transfusion independence/dependence has been defined either varies or has not been explicitly stated across publications [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Transfusions lead to many clinical complications among the MDS population, including infections, transfusion reactions, and iron overload, often leading to dysfunction of end-organ systems such as the heart, liver, and endocrine system [14,[16][17][18]. There is also a significant economic burden associated with transfusion dependence: in a recent analysis, transfusiondependent patients incurred a mean total cost of $17,815 per month vs. approximately $7874 for those patients who were transfusion-independent [15].…”
Section: Introductionmentioning
confidence: 99%